"On slippery ground" – beyond the innocence of collaborative knowledge production. Issue 4 (17th July 2018) - Olesen, Birgitte Ravn; Nordentoft, Helle Merete
Abstract : Purpose: The purpose of this paper is to discuss the ethical complexity and dilemmas, which arise in the co-production of knowledge between researchers and other participants. Design/methodology/approach: The starting point for the paper is a narrative from a conference the authors attended where the authors, as researchers, found themselves on slippery and emotionally charged ground. Using a critical, reflexive approach informed by post-structuralism, the ambition was to deconstruct gaps between rhetoric and practice and critique normative understandings of the nature of ethically sound co-production processes in collaborative research. More specifically, at the conference, the authors sought to expose and discuss the gap between the good intentions and the own practice as researchers in a collaborative research project at a major hospital. However, instead of reflexive discussions with the research community, the authors experienced that the conduct was criticized and categorized as unethical practice. Findings: Instead of omitting sensitive phenomena from the research process, the authors argue that it is an ethical imperative to investigate these phenomena in order to gain insight into what is at stake in dialogical, reflexive processes not only between researchers and research participants—but also between researchers in the research community. An awareness of the emergent nature of power relations in all processes of knowledge production may strengthen the practical validity of "co-produced" knowledge in action research. Originality/value: A poststructuralist perspective on collaborative research processes reveals normative expectations regarding ethical research practice and provides insight into the tensions in collaborative research that arise irrespective of the individual competence (or not) of the researcher.